ANALISIS PERHITUNGAN PAJAK PENGHASILAN BADAN PADA KOPERASI ABC TAHUN 2019 - Jessica Tracy Homy; Purnamawati Helen Widjaja; Henny Henny (Jurnal Paradigma Akuntansi, 2022)
This resarch aims to determine the application of fiscal reconciliation to ABC cooperatives's commercial financial statements in 2019 and find out whether the ABC cooperative has calculated the Corporate Income Tax Payable under the law's current tax. In addition, to compare the calculation of Payable Corporate Income Tax before and after fiscal correction. Data collection was carried out through data documentation and interviews with the cooperative. The method used in this research is descriptive analysis, which is carried out by analyzing the cooperative commercial financial report data and then making fiscal corrections based on the applicable tax regulations. This study indicates that the calculation of Corporate Income Tax payable by ABC Cooperative is not in accordance with applicable tax provisions.Implication of this study that cooperatives need to adjust commercial financial reports with applicable tax laws to produce fiscal financial reports used as the basis for calculating Payable Corporate Income Tax.